WR1065 conjugated to thiol-PEG polymers as novel anticancer prodrugs: broad spectrum efficacy, synergism, and drug resistance reversal - Walker, Dale M.; Lazarova, Tsvetelina I.; Riesinger, Steven W.; Poirier, Miriam C.; Messier, Terri; Cunniff, Brian; Walker, Vernon E. (Frontiers in Oncology, 2023)
A new drug family was developed for intracellular delivery of the bioactive aminothiol WR1065 by conjugating it to discrete thiol-PEG polymers: 4-star-PEG-S-S-WR1065 (4SP65) delivers four WR1065s/molecule and m-PEG6-S-S-WR1065 (1LP65) delivers one. Infrequently, WR1065 has been reported to have anticancer effects when delivered via the FDA-approved cytoprotectant amifostine, which provides one WR1065/molecule extracellularly. The relative anticancer effectiveness of 4SP65, 1LP65, and amifostine was evaluated in a panel of 15 human cancer cell lines derived from seven tissues. Additional experiments assessed the extent that co-treatment with 4SP65 potentiates the anticancer effectiveness and overcomes drug resistance to cisplatin, a chemotherapeutic, or gefitinib, a tyrosine kinase inhibitor (TKI) targeting oncogenic epidermal growth factor receptor (EGFR) mutations. The CyQUANT ® -NF proliferation assay was used to assess cell viability after 48-h drug treatments, with the National Cancer Institute COMPARE methodology employed to characterize dose-response metrics. In normal human mammary epithelial cells, 4SP65 or 1LP65 enhanced or inhibited cell growth but was not cytotoxic. In human cancer cell lines, 4SP65 and 1LP65 induced dose-dependent cytostatic and cytolytic effects achieving 99% cell death at drug concentrations of 11.2 ± 1.2 µM and 126 ± 15.8 µM, respectively. Amifostine had limited cytostatic effects in 11/14 cancer cell lines and no cytolytic effects. Binary pairs of 4SP65 plus cisplatin or gefitinib increased the efficacy of each partner drug and surmounted resistance to cytolysis by cisplatin and gefitinib in relevant cancer cell lines. 4SP65 and 1LP65 were significantly more effective against TP53-mutant than TP53-wild-type cell lines, consistent with reported WR1065-mediated reactivation of mutant p53. WR1065 also is reported to reduce degradation of p53, extending p53 protein activity for 60-70 h. 4SP65 and 1LP65 represent a unique prodrug family for innovative applications as broad-spectrum anticancer agents that target p53 and synergize with a chemotherapeutic and an EGFR-TKI to prevent or overcome drug resistance.b Synergy score data obtained via SynergyFinder (6159); scores < -10 likely antagonistic, -10 to +10 likely additive, and >10 likely synergistic on a scale of 60. * P <0.05, ** P <0.01, *** P <0.001